The role of strategic management in government organizations to achieve sustainable development (International Journal of Financial, Administrative and Economic Sciences, 2025)
The application of strategic management in government organizations is an imperative necessity to become efficient and effective in facing internal and external environmental variables and interacting with citizens. To provide outstanding products and services; in a way that contributes to achieving sustainable development in light of the state’s vision 2030. This study aimed to identify the nature of strategic management in government organizations, the basic concepts related to sustainable development, as well as sustainable administrative development by analyzing the situation to apply strategic management and its role in achieving sustainable development in its dimensions (economic – social – environmental).        The study used the descriptive analytical approach in studying the relationship between variables and was applied government organizations. They are represented by the Saudi Ministry of Commerce and its relationship with achieving Vision 2030 in sustainable development, which aims for a vibrant society that enjoys a full and healthy life, empowering members, focusing on its strengths, and exploiting the available opportunities to create a diverse and prosperous economy.
Keywords: Strategic Management; Governmental Organization; Sustainable Development; Sustainable Administrative Development